Single-step extraction of bioactive compounds from cruciferous vegetable (kale) waste using natural deep eutectic solvents - Lee, Sze Ying (2023)
Cruciferous vegetables such as kale contain various health-promoting phytochemicals, and leaves rejected from harvesting could be a valuable source of phytochemicals. Conventional organic solvents used for the recovery of these bioactive metabolites are hazardous, and therefore more benign equivalents are sought. This work explores the use of natural deep eutectic solvents (NADESs) with different hydrophilicity/hydrophobicity to recover polyphenols, carotenoids and chlorophylls from kale waste. Enhanced extraction of polyphenols was achieved by the aqueous solutions of hydrophilic glycerol-based NADESs, with yields of up to 2.2-fold higher than just using methanol. The antioxidant capacity of the aqueous extracts showed a strong correlation with their total phenolic contents. The best solvent in extracting polyphenols (glycerol:betaine at a molar ratio of 3:1) was further investigated to optimise its process conditions. The optimised extract provided the greatest stability of the bioactive polyphenols by retaining 91.7 and 88.6% of the original contents after 30 days of storage at 4 and 25 °C, respectively. Furthermore, this extraction approach was integrated with ethyl acetate, a bio-based solvent, to promote the simultaneous recovery of polyphenols (16.83 mg GAE (gallic acid equivalents) g-1 DW (dry weight)), carotenoids (0.91 mg g-1 DW) and chlorophylls (7.86 mg g-1 DW) from kale waste. After extraction, the immiscible aqueous NADES- and ethyl acetate-phases rich in polyphenols and carotenoids/chlorophylls, respectively, can be easily separated for different applications.